Body exhibition or idyllic imagination? Female microcelebrities in mobile short videos depicting the Chinese countryside - Chen, Maichi Match; Dong, Yan; Zhang, Jun; Qu, Guichun; Sun, Zonglin; Jiang, Yanmei; Hu, Guili (Frontiers in Communication, 2025)
Mass communication in the We Media era has redefined China's rural virtual community and transformed the representation of the female body in the countryside. Using research methods such as literature review, case studies, and content analysis, this study adopts perspectives from the sociology of the body and feminist media studies to explore how female microcelebrities and social media influencers (SMIs) use their bodies to present authentic rural life. The research highlights their significant roles in marketing the countryside, fostering idyllic imaginations for mass audiences, and supporting rural revitalization. Focusing on prominent examples such as Li Ziqi, we argue that female microcelebrities endorsed by both the state and netizens contribute to rural marketing by promoting web traffic, agricultural products, and stronger idyllic imagery, thereby advancing China's rural revitalization efforts.